A new role for the non-aligned movement in a post-cold war era - Chetty, Mahesh (Rhodes University, Faculty of Humanities, Department of Political Studies, 2000)
With the disappearance of the superpower conflict that characterised the Cold War era, many observers have begun to question whether the Non-Aligned Movement (NAM) has a role to play in the post Cold War era. However the emergence of a number of issues on the international agenda, such as United Nations peacekeeping operations, global environmental issues and an increasing unwillingness on the part of the major economic powers to abide by GATT/WTO rules, have increasingly become of concern to non-aligned states. However whilst the United States has recognised that these issues require leadership in dealing with them, it has not been willing to supply that leadership. It shall therefore be argued that the changing nature of hegemony in world politics has set conditions that allow non-aligned middle powers and institutions greater scope for action and influence. The emergence of these issues has provided a scope for non-aligned middle powers, acting in accordance with their interests to play alternate leadership roles within an expanded scope for institutions, such as organisations, regimes and multilateralism, in addressing the interests of non-aligned states. Firstly in looking at an expanded role for organisations, the United States has increasingly been unwilling to play a leadership role within UN peacekeeping operations. The continuing importance of the neutrality of UN peacekeeping operations has provided a scope for nonaligned middle powers to play a burden-sharing role with the great powers in addressing the concerns of non-aligned states with regard to these operations. Secondly in looking at an expanded scope for regimes, the emergence of a regime in the issue of ozone depletion may provide a foundation to analyse how non-aligned middle powers may play a bridge-building role between North and South in the issue of climate change. Middle powers could therefore play this role in the absence of United States leadership within this issue. Thirdly, the role of the Cairns Group within the Uruguay Round in addressing non-aligned states' interests of maintaining stable agricultural trade, can be seen as a model of small group multilateralism in bridging the divide between the major powers in issue specific areas.
Keywords: Non-Aligned Movement|Nonalignment|Nonalignment -- Developing countries|International police